Supply and Demand Matching of Financial Support Policies for Private Enterprises Based on Text Measurement - Wei Liu; Jun Gu; Rong Zhang; Yi Yang (Discrete Dynamics in Nature and Society)
The degree of matching between supply and demand for financial support policies is a key factor for policy effectiveness. In this paper, we use policy text computing method that integrates topic mining, text classification, and training set predictions to study the supply and demand matching of China’s financial support policies for private enterprises. We find that supply and demand match for policies on diversified financing channels. However, there is mismatch in financial service facilitation policies and local subsidy policies. Our research implies that China’s development of a multiple-layer financial market has promoted the diversification of financing channels, which has improved the financing conditions for private enterprises. However, financial service network is still not convenient to facilitate private enterprises.